Perception and Utilization of Indigenous Knowledge Books on Research Productivity Among LIS Lecturers in Kwara State - Akinbowale, Aishat Temitope; Adesina, Yunus Ismail; Saliu, Abdulfatai; Oyeniran, Segun Adisa; Hammed, Mujeeb Olujide (Jurusan Ilmu Perpustakaan dan Informasi Islam Universitas Islam Negerin Datokarama Palu, 2025)
The study examined the perception and utilization of indigenous knowledge books on research productivity among LIS lecturers in kwara state. It adopted descriptive survey design and population for this study consists of all LIS lecturers in five selected University in Kwara State. The target population for this study is 57 lecturers in the department of library and information science. Hence, total enumerative sampling technique was adopted. Questionnaire was used as data collection instrument and percentages and mean are used in analyzing data. The study revealed that majority of the lecturers in kwara state have a positive perception of indigenous knowledge books with the option of it is important to improve research productivity. Also, it revealed that indigenous knowledge books are important to improve research productivity to a high extent. It further revealed that indigenous knowledge books promote users/researchers confidence and it brings together different materials on the same subject. Lastly, no up to date materials, poor library instruction are some of the major challenges LIS lecturers encounter while using indigenous knowledge books for their research productivity. The study concluded with recommendations such as University management should ensure that necessary facilities that enhance high level of utilization of indigenous knowledge books are adequately provided and Lecturers should be regularly informed of newly acquired Indigenous book.